Digitex futures - Pták, Radim (2020)
Digitex futures exchange is a start-up company in the cryptocurrency space that promises to develop a futures exchange that does not need to charge trading fees in order to raise funds to cover operating expenses.The goal of the thesis is to explain the mechanics of raising funds via the DGTX token and come up with ideas to improve the overall value of the token in the future.